Citrus Flavonoid Effects on Obesity - Yu Wang; Laura E. Reuss (EDIS)
The increased prevalence of obesity in recent decades has sparked tremendous concern worldwide. Obesity, a chronic disease that increases the risk for a myriad of diseases including diabetes, hypertension, cardiovascular diseases, as well as certain types of cancers, results from a persistent excess of energy intake versus energy expenditure and is characterized by an increase in both adipose cell size and number. Treatments to date consist of medications that cause various adverse side effects. This has led to the recent shift in focus towards investigating natural alternatives to treat obesity. The use of phytochemicals as a safe and natural alternative to treat obesity is under current investigation as citrus flavonoids haven been shown to monitor energy intake versus expenditure, regulate lipid metabolism and adipose tissue, and inhibit amylase function.